2023
DOI: 10.3389/fcvm.2023.1074661
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between baseline D-dimer and prognosis in Japanese patients with venous thromboembolism: Insights from the J’xactly study

Abstract: BackgroundD-dimer is a biomarker of fibrin production and degradation, and changes in D-dimer concentration suggest fibrin clot formation, which is associated with thromboembolism and hypercoagulable states. Thus, an elevated D-dimer concentration could be a useful prognostic predictor for patients with venous thromboembolism (VTE).Methods and resultsIn this subanalysis of the J’xactly study, a prospective multicenter study conducted in Japan, we examined the clinical outcomes of 949 patients with VTE stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“… 17 , 18 An elevated risk of VTE is linked to elevated D-dimer levels. 19 , 20 D-dimer is a biomarker that shows promise in determining a stroke patient's likelihood of developing secondary VTE. 19 , 21 , 22 Furthermore, a study stratifying patients with different types of solid tumors according to VTE risk found that certain types of solid tumors (esophageal, lung, melanoma, ovarian, pancreatic, gastric, and uterine) were associated with a higher incidence of VTE compared to other cancer types (6.8% vs 3.9%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 An elevated risk of VTE is linked to elevated D-dimer levels. 19 , 20 D-dimer is a biomarker that shows promise in determining a stroke patient's likelihood of developing secondary VTE. 19 , 21 , 22 Furthermore, a study stratifying patients with different types of solid tumors according to VTE risk found that certain types of solid tumors (esophageal, lung, melanoma, ovarian, pancreatic, gastric, and uterine) were associated with a higher incidence of VTE compared to other cancer types (6.8% vs 3.9%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%